THE SCIENCE OF BODY LANGUAGE - Rakhimova, Komila (Журнал иностранных языков и лингвистики, 2023)
Body language is a form of non-verbal communication. Body language is about using behavior to communicate. Both people and animals use this form of communication. Part of this behavior is done subconsciously. It is therefore different from communicating using sign language, for example. Communication using sign language is intentional, body language is not. It helps teachers understand what their students are thinking and feeling. In fact, body language is so important that it should be included in teacher training.